Brazil : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper analyzes pace of economic growth for Brazil. Moderating activity and stubbornly elevated inflation since 2010 have led to a reevaluation of Brazil's long-term potential growth rate. Growth accounting suggests that potential growth is probably lower than was widely assumed in recent years and now stands at about 3 1\2 percent. The demographic dividend of a rapidly expanding labor force is fading and further structural declines in unemployment are likely to be limited. Potential growth will rely more on the pace of capital deepening and productivity growth. Lifting both may require successful implementation of the infrastructure investment program, higher domestic saving, and structural reforms.